Trusting Online Reviews Enhances Intention to Book Online: The Perks of Seeking Information? - Zahidah, Shafira Rahma; Rostiani, Rokhima (Jurnal Manajemen Bisnis, 2021)
Research aims: This study aims to analyze factors affecting consumer intention to book hotels from social media and online travel agencies. Specifically, we examine the direct effects of social media usage and electronic word of mouth (e-WoM) and the indirect effect through the mediation of trust in booking intention.Design/Methodology/Approach: Purposively sampled respondents resulted in 409 responses that met the predefined criteria: aged 18-34, active on their social media accounts, and had accessed online booking sites. Regression with mediating analysis was conducted on valid data.Research findings: Analysis results showed that social media usage and e-WoM had a direct, positive, and significant impact on booking intention. It has also proven to have an indirect effect on consumer booking intention mediated by trust. Social media usage and e-WoM directly affected booking intention and had higher valence when mediated by trust.Theoretical contribution/Originality: Information on social media positively influenced consumer purchase intention on online hotel booking due to its completeness. Further, this study is among the few that applied the e-WOM concept to the hospitality sector.Practitioner/Policy implication: The implication for managers is to improve the online booking management system by increasing promptness in response to reviews, especially the negatives.Research limitation/Implication: This study focused on consumers who have social media accounts and accessed online hotel booking sites, limiting its generalizability.